Tax Havens and Global Income Inequality - Yildiz, Abdunnur; Demir, Murat (Maliye Bakanligi, 2019)
As a result of the developments in globalization and information technologies, there has been an increase in the tax competition among countries. This competition is especially experienced among countries trying to attract foreign capital investments into their countries. There are many different forms of tax competition, but one of the most widely used methods is tax havens. Tax havens are used extensively by multinational corporations and rich individuals, and this leads to the erosion of tax revenues in some countries. In this study, data on the amount of global wealth held in tax havens is examined. As a result of the study, it was concluded that tax havens increased global income inequality; and the share of the poor from global welfare/wealth decreased day by day.
Keywords: Tax Evasion; Tax Avoidance; Tax Havens; Global Income Inequality